Do cover crops improve the productivity and industrial quality of upland rice? - Portugal, José R. [UNESP]; Arf, Orivaldo [UNESP]; Buzetti, Salatiér [UNESP]; Portugal, Amanda R.P. [UNESP]; Garcia, Nayara F.S. [UNESP]; Meirelles, Flávia C. [UNESP]; Garé, Lucas M. [UNESP]; Abrantes, Fábio L. [UNESP]; Rodrigues, Ricardo A.F. [UNESP] (Wiley, 2020)
Global rice (Oryza sativa L.) cultivation is expected to increase, especially in upland no-tillage systems (NTS). The difficulty in producing and maintaining straw in NTS in the Brazilian Cerrado and comparative regions worldwide can be overcome by using cover crops in irrigated areas. The potential of straw accumulation, soil cover maintenance, and nutrient cycling is considered while choosing cover crop species, because these characteristics may interfere with subsequent crop cultivation. This study was conducted to determine whether cover crops could benefit the development, productivity, and industrial quality of upland rice grains irrigated by sprinklers and cultivated in succession. The experiment was conducted in the Cerrado, with a summer rainy season and a dry winter. The treatments consisted of six cover crops (millet [Pennisetum glaucum], sunn hemp [Crotalaria juncea], pigeonpea [Cajanus cajan], millet + sunn hemp, millet + pigeonpea, and fallow) sowed in winter or spring. Compared to fallow, the cover crops cultivated in winter or spring led to increased straw production, accumulation of approximately 150% more nitrogen in straw, and possibly improved rice nutritional value because of the higher N content. Rice plants cultivated after sunn hemp developed a greater dry mass than rice cultivated after the fallow treatment. Grain yield was not influenced by the cover crops. However, sunn hemp cultivation increased the milling yield, head rice yield, and the milled rice productivity (MRP), compared to cultivation following the fallow treatment. Cultivation of sunn hemp before the upland rice crop improved MRP compared to that following the fallow treatment.